El proyecto educativo institucional y el desarrollo académico y administrativo, del centro de educación básica Lauro Damerval Ayora n° 1, de la parroquia San Sebastián, del cantón y provincia de Loja, en el período 2012-2013. Lineamientos alternativos - Cueva Figueroa, Galo Vinicio (2014)
This research is the following problem: how affects the Institutional Educational Project in the academic and administrative development of the Center for Basic Education "Lauro Damerval Ayora Nº. 1", from the San Sebastian parish, canton and province of Loja, in the period 2012-2013 in the same?, has set a goal to establish the incidence of institutional educational project in the academic and administrative development of the Center for Basic Education Lauro Damerval Ayora N ° 1. The methods used were: Deductive, Inductive and Analytical, which allowed them to know the reality of the problem investigated, obtain the appropriate information, and content, the techniques used were: Steering interview, surveys of teachers and parents the school. The results allowed us to conclude participation in making the diagnosis for Institutional Educational Project construction is minimal, therefore the mission designed not to define the institutional image, and secondly that performs management is poor management in generating specific projects implementation and change in academic development, the code of living, has sporadic commitments to improve the working environment in the institution, as well as the Internal established does not allow the harmonious operation of the establishment and institutional strengthening.